The fiscal regime for deep sea mining in the Pacific region. (September 2018) - Mullins, Peter; Burns, Lee
Abstract: Deep sea mining has the potential to raise much needed revenue for Pacific Island States. This will require national governments to implement a comprehensive fiscal regime for deep sea mining comprising pay-as-you produce and profit-based instruments. The aim of this article is to explain the design of the main fiscal instruments relevant to deep sea mining activities, focusing particularly on mining royalties, corporate tax, and resource rent taxation. Highlights: The Addis Tax Initiative highlighted the need for DRM of developing countries. For some Pacific Island States, the opportunity to mobilise substantial revenue from DSM activities could be transformative. To this end, the implementation of an effective fiscal regime is essential.